Social Discrimination: A Case Study of Social Subordination to Eastern Vernacular Indonesian Speakers - Ayudhia Ratna Wijaya; Cesar Abdul Rizal (Universitas Sebelas Maret, 2023)
This research aims to explain the correlation between Bahasa Indonesia’s vernacular variation and the social discrimination experienced by Eastern Indonesian. The researchers apply qualitative-quantitative method. The data were collected from the distributed online questionnaires which were filled by 41 respondents from Eastern Indonesia (East Nusa Tenggara, Sulawesi, Maluku, Papua). The findings show that there is a diglossic phenomenon between standard Bahasa Indonesia (High variety) and Bahasa Indonesia of Vernacular Eastern Indonesia (Low variety). The unique dialectal characteristics of Eastern Indonesian in Bahasa (phonological, lexical, and morphological) raised the issue of linguistic racism and linguistic privilege. Eastern Indonesian speakers of Bahasa are considered as minority speech community who suffered racism and discrimination. They experienced intimidation from people’s undermining impersonation, underestimation, and exclusion from the dominant speech community. They felt ashamed of their vernacular language identity and tend to imitate dominant accents, such as Javanese or Jakartan Indonesian. This is a serious issue that can increase social disparities and conflict among Indonesians. To solve the problem, the researchers suggest that Indonesian government must introduce Bahasa Indonesia’s variation (including morphological, lexical, and phonological variation from all Indonesian region) in the formal education as the best solution to give societies understanding of linguistic tolerance.